Analysis of stress-deformed state of flexible shells complex configuration - Цихановський, В.К.; Костира, Н.О. (Proceedings of National Aviation University (archive), 2006)
The strained-deformed state of the thin-walled combined structures was searched. The basic element of such structures is the flexible thin shells with ribs and inserts: curvilinear thin-walled pipes, equalizers, shell with edges. Researches of loss of local stability outside elasticity are executed.